EFFECT OF DRYING METHOD ON PHYSICOCHEMICAL PROPERTIES OF PUMPKIN FLOUR - et al., Mardiah Mardiah (International Journal of Advanced Science and Technology, 2020)
Yellow pumpkin is one of the most abundant foodstuffs in Indonesia. One of its uses is to becomeflour so that it can be used as a base for food preparations and can be stored in the long term. Thisstudy aims to determine the effect of the drying method on physicochemical properties and nutrientcontent and β-carotene in pumpkin flour. This study uses two methods of drying tray drying and drumdrying with three varieties of pumpkin, namely Cucurbita maxima D, Cucurbita maxima L andCucurbita moschata. The results showed that drying tray drying and drum drying did not providesignificant data differences in water content, protein content, ash content, carbohydrate content andfiber content of pumpkin flour produced from three varieties. But the drying method makes a differenceto the fat content of pumpkin flour. The range of starch water content in three pumpkin varieties isbetween 11% -22.67%, ash content 9.39% -11.95%, protein content 6.06% -16.57%, fat content 1.3%-6.58%, carbohydrate content 65.47% -80.35%, crude fiber 8.21 % -21.55%. The drying method doesnot give different data on the content β carotene of pumpkin flour. The β carotene content of pumpkinflour ranges from 0.84 mg / g-2.8 mg / g. The drying method yields different water absorption and bulkdensities on Curcubita maxima D flour. The absorption capacity of pumpkin flour ranges from 6.86 ml/ g-9.41ml / g. Bulk density of flour is between 0.56 g / ml-0.75 g / ml and flour yield based on the totalweight of fruit ranges between 6.29% -10.11%. The drying method does not make a difference in thebrightness value of the flour, but produces a difference in the value of a (redness) and b (yellowness).The brightness value of flour (L) ranges from 72.41-85.57, the value of a * range from 7.86-21.79, thevalue of b * ranges between 44.14-59.5. In the gelatinization profile analysis, the drying method givespeak viscosity data and gelatinization time is significantly different in the resulting pumpkin flour. Thepeak viscosity of pumpkin flour ranged from 1298cP to 3964cP, through ranged from 1303cP-177 cP,Final viscosity ranged from 1941cP to 3342 cP, peak time ranged from 2.3 to 13 seconds, and pastingtemperature between 50.1-93.4oC. Conclusions from the results of the study this drying method affectsphysical and chemical properties in pumpkin flour